Penguins / Barbara Taylor - Taylor, Barbara (First Q & A, 2014)
Explore the harsh, icy world of penguins and their clever survival techniques. Discover everything you need to know about these amazing birds with this brilliant book. One hundred facts, fantastic illustrations, and hilarious cartoons reveal the different types of penguins, while fun quizzes test your knowledge.